Uveitis of Unknown Etiology: Clinical and Outcome features. A Retrospective Analysis of 355 Patients. (17th November 2019) - Richard Colmant, Gaëlle; Kodjikian, Laurent; De Parisot De Bernecourt, Audrey; Guillaud, Martin; Gerfaud-Valentin, Mathieu; Denis, Philippe; Broussolle, Christiane; Jamilloux, Yvan; Sève, Pascal
ABSTRACT: Purpose : Despite the huge advance in diagnostic technics, about one-third of uveitis is still considered of unknown etiology. In this study, we aimed to report their clinical features and to describe how a diagnosis has been finally reached for some patients. Methods : We retrospectively reviewed all patients with uveitis referred to our tertiary center between 2002 and 2016. The unknown etiology was admitted after a new ophthalmologic examination and a full work-up in internal medicine in our tertiary center. Results : Among 957 patients with uveitis, 355 had uveitis of unknown etiology. The clinical and epidemiological characteristics of this subgroup were no different from those with a known etiology. Out of 104 patients who were followed-up for more than 1 year, a diagnosis was finally achieved in 20 patients. The diagnosis was determined either because of the occurrence of a new clinical symptom ( n = 10), a new/repeated non-ophthalmologic investigation ( n = 7), or a new/repeated ophthalmic exam ( n = 3). Conclusion : A prolonged follow-up, with repeated exams, may allow the determination of an etiology in about one-fifth of uveitis initially considered as idiopathic.